Improvement study on the rapid hardening epoxy mortar. Issue 1 (July 2021) - Hu, Jiayu; Ge, Jinyu; Yao, Huaizhu; Wei, Hua; Li, Jiaming; Xu, Zhiqiang
Abstract: Mechanical properties of epoxy resin mortar with different proportions were tested based on orthogonal method. The influences of each factor on the compressive strength, flexural strength and bond strength of epoxy resin mortar after 1 day were analyzed by extremum difference analysis. The results indicated that the diluents occurred the highest influence on the mechanical properties of the epoxy mortar; the mass ratio of cement to sand (C/S) mainly affected the bond strength of the epoxy mortar; the increasing curing agent content would reduce the toughness of mortar. Based on the orthogonal analysis, the optimum proportion of the epoxy mortar was determined, which included a ratio of filler to liquids (F/L) of 2: 1, a curing agent dose of 100% (referenced by the mass of epoxy resin), a C/S of 2: 1 and a diluent dose of 10%.